A Triazinone Derivative Inhibits HIV‐1 Replication by Interfering with Reverse Transcriptase Activity. (16th September 2016) - Urano, Emiko; Miyauchi, Kosuke; Kojima, Yoko; Hamatake, Makiko; Ablan, Sherimay D.; Fudo, Satoshi; Freed, Eric O.; Hoshino, Tyuji; Komano, Jun
Abstract: A novel HIV‐1 inhibitor, 6‐( tert ‐butyl)‐4‐phenyl‐4‐(trifluoromethyl)‐1 H, 3 H ‐1, 3, 5‐triazin‐2‐one (compound1 ), was identified from a compound library screened for the ability to inhibit HIV‐1 replication. EC50 values of compound1 were found to range from 107.9 to 145.4 nm against primary HIV‐1 clinical isolates. In in vitro assays, HIV‐1 reverse transcriptase (RT) activity was inhibited by compound1 with an EC50 of 4.3 μm . An assay for resistance to compound1 selected a variant of HIV‐1 with a RT mutation (RT L100I ); this frequently identified mutation confers mild resistance to non‐nucleoside RT inhibitors (NNRTIs). A recombinant HIV‐1 bearing RT L100I exhibited a 41‐fold greater resistance to compound1 than the wild‐type virus. Compound1 was also effective against HIV‐1 with RT K103N, one of the major mutations that confers substantial resistance to NNRTIs. Computer‐assisted docking simulations indicated that compound1 binds to the RT NNRTI binding pocket in a manner similar to that of efavirenz; however, the putative compound1 binding site is located further from RT K103 than that of efavirenz. Compound1 is a novel NNRTI with a unique drug‐resistance profile. Abstract : Resisting resistance : A novel non‐nucleoside reverse transcriptase inhibitor (NNRTI, shown) was identified. Its EC50 values range from 107.9 to 145.4 nm against various primary HIV‐1 clinical isolates, and is effective against HIV‐1 with the K103N RT mutation, which confers substantial resistance to NNRTIs in current use. This compound has a unique drug‐resistance profile and shows synergistic effects against HIV‐1 in combination with other antiretroviral drugs, and could therefore serve as a lead for the development of novel NNRTIs.